Carbon composite of NiO hydrothermal impregnation from sugarcane bagasse and its electrochemical properties - Nasti, Al Nadine De; Siburian, Kyfti Yolanda; Sembiring, Abraham Danofan; Kristianto, Hans; Susanti, Ratna Frida; Oktaviano, Haryo Satriya; Nugroho, Agung (Jurnal Rekayasa Proses, 2023)
Sugarcane bagasse (SB) can synthesize activated carbon (AC) through a two-step calcination process at calcination at 400oC and activation at 800oC. NaOH 0.1 M is used to activate the pre-carbonized sample in the activation step. The AC samples undergo hydrothermal impregnation with nickel oxide (NiO) at 110°C. The X-ray diffraction (XRD) pattern and Energy dispersive X-ray spectroscopy (EDX) confirmed the presence of NiO after this process. Scanning Electron Microscope (SEM) indicates the presence of pore structures in the sample morphology. A three-electrode system with 1 M Na2SO4 as an electrolyte was employed to assess the electrochemical properties. The specific capacitance for activated carbon derived from SB stands at 89.53 F/g at 0.05 A/g current density, while after impregnation with NiO, it increases to 250.53 F/g at the same current density. The results demonstrate the possibility of activated carbon from sugarcane bagasse waste composited with NiO as supercapacitor electrodes.